Academic league in women’s health: Creation, legalization and impacts on future nurses (Research, Society and Development, 2025)
Objectives: To report on the creation and legalization of the Academic League of Women's Health and Female Empowerment, highlighting its contribution to the academic training of nursing students. Methods: Descriptive study in the form of an experience report, conducted through documentary analysis of the League's records and oral accounts from its members. Data analysis revealed three thematic axes: the foundation and structuring of the League, the activities carried out, and the observed impacts on the academic community. Results and discussion: The League was conceived and founded in response to demands from students in the nursing and psychology undergraduate programs. As a result, the project for its creation was presented at a 2020 meeting of the Nursing Department of the educational institution, during which the project's justifications and objectives were outlined. Following approval, its bylaws were drafted and officially recognized by a notary. Conclusion: The creation and activities of the League support academic growth, enhance student autonomy, and promote research, teaching, and outreach initiatives that benefit not only the academic community but also the broader public. Thus, the League enables curricular development, lifelong education, and the implementation of practices aimed at health promotion.